Cryogenic vs. absorption biogas upgrading in liquefied biomethane production – An energy efficiency analysis. (1st June 2019) - Hashemi, Sayed Ebrahim; Sarker, Shiplu; Lien, Kristian M.; Schnell, Sondre K.; Austbø, Bjørn
Highlights: Modeling and simulation of two different concepts for liquefied biomethane production. Comparative energy assessment of cryogenic and absorption-based biogas upgrading. Higher overall energy efficiency observed for cryogenic biogas upgrading. The major part of the energy input is used in the liquefaction process. Abstract: Production of liquefied biomethane (LBM) from biogas comprises two major energy intensive processes; upgrading to increase the methane concentration and refrigeration to liquefy the upgraded biogas. Amine-based absorption has been considered an attractive option for biogas upgrading in industrial applications. The temperature increase associated with amine regeneration is, however, in conflict with the cooling requirement of the subsequent liquefaction process. Hence, cryogenic biogas upgrading, integrated with liquefaction, has emerged as an interesting alternative. In this paper, a rigorous energy analysis was performed for comprehensive models of the two aforementioned LBM production alternatives. Both processes were modeled using Aspen HYSYS ® and optimized to minimize the energy use. The results indicate that the integrated cryogenic upgrading process is favorable in terms of both overall energy efficiency and methane utilization. Moreover, the energy analysis implies that the liquefaction process accounts for the major part of the energy input to an LBM plant, demonstrating the significance of improving the energy efficiency of the liquefaction process in order to improve the overall performance of the LBM process.